Aspects Related to Compliance with the Use of Personal Protective Equipment (PPE) in Workers at PT X - Hasanatun Laili Laili; Mayumi Ershanda; Hubban Fathani Manik; M.Syaufi Syukri Handoyo; Zahra Ananda; Zahrani Nabilah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2025)
The use of PPE is still often found by workers who are not compliant in using it. Many factors cause workers to be non-compliant in using personal protective equipment even though the company has provided PPE and implemented regulations that require workers to use PPE. This research was conducted using a quantitative approach with a cross sectional design. The population in this study were all production workers totaling 40 people. Sampling with total sampling technique with data collection methods using primary data in the form of observations and interviews, data collection instruments using questionnaires, data analyzed using the colleration test with a significant level of α = 0.05. The results of statistical tests found that there is a relationship between age and compliance with the use of PPE obtained a p value of 0.001, and there is a relationship between supervision and compliance with the use of PPE obtained a p value obtained of 0.001. Based on the results of the research conducted, it can be concluded that there is a significant relationship between age and supervision on compliance with the use of PPE.